Genetic approaches in preeclampsia - Yong, H.; Murthi, P.; Brennecke, S.; Moses, Eric (2018)
Preeclampsia (PE) is a serious hypertensive disorder that affects up to 8% of all pregnancies annually. An established risk factor for PE is family history, clearly demonstrating an underlying genetic component to the disorder. To date, numerous genetic studies, using both the candidate gene and genome-wide approach, have been undertaken to tease out the genetic basis of PE and understand its origins. Such studies have identified some promising candidate genes such as STOX1 and ACVR2A. Nevertheless, researchers face ongoing challenges of replicating these genetic associations in different populations and performing the functional validation of identified genetic variants to determine their causality in the disorder. This chapter will review the genetic approaches used in the study of PE, discuss their limitations and possible confounders, and describe current strategies.